Fintech, cryptoassets, and central bank digital currency in the Republic of Korea - Ohik Kwon; Jongik Park; Byoung-Ki Kim (Asian Development Bank Institute (ADBI), 2019)
In this study, we describe the fintech and cryptoassets-related trends in the Republic of Korea and review the measures and assessments of the Government of the Republic of Korea and the Bank of Korea. We also provide discussion on central bank digital currency. Fintech in the Republic of Korea still accounts for only a small share of payment and settlement services, but it can induce changes in the financial industry. It is, however, unlikely that cryptoassets will become widely used and accepted in the near future, and the Bank of Korea is taking a cautious stance on central bank digital currency.
Keywords: G2; G15; O16; 330; fintech; cryptoassets; central bank digital currency